Multielement and chemometric analysis for the traceability of the Pachino Protected Geographical Indication (PGI) cherry tomatoes. (30th August 2022) - Giorgia Potortì, Angela; Francesco Mottese, Antonio; Rita Fede, Maria; Sabatino, Giuseppe; Dugo, Giacomo; Lo Turco, Vincenzo; Costa, Rosaria; Caridi, Francesco; Di Bella, Marcella; Di Bella, Giuseppa
Graphical abstract: Highlights: PGI and Not PGI cherry tomatoes belonged to cv "Naomy" were investigated for traceability purposes. Protected and not protected cherry tomatoes from different production areas were considered. Mineral profiles were determined by ICP-MS and analyzed by PCA and CDA. The approaches could be used to guarantee the PGI products from food fraud. Lycopersicon esculentum PGI fingerprint was realized thanks to inorganic markers. Abstract: To prevent PGI (Protected Geographical Indication) cherry tomato of Pachino (Sicily, Italy) from frauds, an alternative method, which includes chemometric treatments, was proposed. The content of 32 inorganic elements (macro-micronutrients and lanthanides) present in 16 PGI and 24 not PGI cherry tomato samples cv Naomy, and in 16 PGI and 8 not PGI soil samples, was determined by Inductively Coupled Plasma - Mass Spectrometer (ICP-MS). To identify the elements able to differentiate PGI and not PGI cherry tomato samples, Principal Components Analysis (PCA) and Canonical discriminant analysis (CDA) were performed. The first two principal components (PC1-PC2) explain a total variance of 71, 41% between PGI and not PGI group, whereas CDA showed Zn, Cd, Mn and Ca as inorganic markers able to correctly classify the 100% of samples. Furthermore, with a translocation factor (K), evaluated in soil/plant chain, the comparison of absorption trends for PGI and not PGI samples was realized.